Izbrannye voprosy identifikacii, otbora i razvitija futbol'nogo talanta v kontekste soveršenstvovanija trenerskoj praktiki (obzor naucnych issledovanij) - Guba, V. P.; Kromke, K.; Stula, A.; Antipov, A. V. (Vestnik sportivnoj nauki; Sports science bulletin, 2020)
The article is devoted to the review of scientific research essential for coaching practice on the identification of football talent and its development. The presented research results make it possible to distinguish elite athletes and amateur players, as wellas determine the conditions for the process of identifying football talent, the possibility of selection, attraction and management during comprehensive training of young players in football. The cited examples and statistics speak in favor of effective scientifically sound methods of working with gifted football players, and also confirm the need for the further professional growthof coaches working with promising young football players.Keywords: football, identification, selection, development of talent, signs of talent, coaching practice.